Public-Private Partnerships in e-Government : Knowledge Map - Institute for Public-Private Partnerships (World Bank, Washington, DC, 2014)
The last few years have seen considerable research and applications in the areas of Public-Private Partnerships (PPPs) and electronic-government (e-government). Rather than attempting to redefine these areas, or considering them as two distinct paradigms, the authoring of this Knowledge Map (KM) and its accompanying Handbook is an effort to bring a certain degree of convergence, and see whether PPPs are, or can be, effective instruments for e-government initiatives in a country. The increasing emphasis on e-government is often directly attributed to the fact that the use and application of Information and Communication Technologies (ICT) are now commonly accepted as powerful engines for economic growth. As governments embrace ICT as a means to accelerate the development process this also becomes foremost in the reforms agenda, and in their delivery of services to citizens, businesses, civil society organizations, and other government agencies. This 'public-private partnerships in e-government: knowledge map' is designed to be an introductory guide to PPPs for public officials responsible for e-government initiatives. It is for those who are seeking to enhance the quality, efficiency, and affordability of those initiatives by employing PPPs.